Link-N Exerts Its Growth Factor-Like Effects through Activation of Smad 1/5 Signaling in Human IVD Cells. (May 2014) - Mwale, F.; Madiraju, P.; Haglund, L.; Roughley, P. J.; Antoniou, J.
Introduction: Back pain is a fairly common problem, which affects a large portion of the population and has an impact on quality of life. Intervertebral disc (IVD) degeneration is one of the most common causes of back pain. Link-N peptide represents the 16 amino acid sequence (DHLSDNYTLDHDRAIH) from the N-terminus of the link protein that stabilizes the proteoglycan aggregates present in cartilage and IVDs. We have previously shown that Link-N can stimulate collagen and proteoglycan synthesis in IVD cells in vitro 1 and in intact human IVDs ex vivo, 2 as well as increase disc height in a rabbit model of disc degeneration. 3 Recently, BMPII receptor has been shown to interact with Link-N in rabbit IVD cells. 4 The purpose of this study was to determine the mechanism by which Link-N exerts its beneficial effects by promoting matrix production in human IVD cells. Materials and Methods: Human lumbar spines were retrieved through the Transplant Quebec organ donation program. IVD cells were isolated from nucleus pulposus (NP) and annulus fibrosus (AF) regions. The cells were cultured to 90% confluence in NP Cell Medium (NPCM, Cat. No.4801, ScienCell). Then the cells were incubated overnight in serum-free DMEM followed by treatment with Link-N (1 μg/mL), TGF-β (10 ng/mL) or BMP-2 (25 ng/mL) for 10 minutes to 4 hours. TGF-β (10 ng/mL) or BMP-2 (25 ng/mL) was used as positive controls. Cell extracts were prepared using NP40 lysis buffer. Total protein in the cell extracts was determined by the bicinchoninic acid assay (BCA). Protein expression was analyzed by immunoblotting using specific antibodies. Western blot images were quantified using ImageJ (NIH) software. For gene expression studies, cells were incubated for 24 hours with Link-N (1 μg/mL) in the presence or absence of human recombinant noggin (100 ng/mL) and total RNA was isolated using Trizol reagent and relative gene expression was determined by RT PCR. For receptor-binding studies, AF and NP cells were treated with biotinylated Link-N (1 μg/mL) with or without untagged Link-N (10 μg/mL) for competitive displacement. Scrambled biotinylated Link-N (1 μg/mL) was used as a specificity control. After treatments, cells were fixed in 2% paraformaldehyde. Fixed cells were treated with fluorescent-dye conjugated streptavidin (Alexa Fluor 700 conjugate, streptavidin). We assessed whether noggin directly binds with biotinylated Link-N by dot-blot technique. Results: Link-N addition to human IVD cells did not promote the phosphorylation of Smads 2 and 3. This suggested that Link-N signaling does not function in a fashion similar to TGF-β, which stimulates the phosphorylation/activation of Smads 2 and 3. Further, similar to BMP-2, Link-N promoted the phosphorylation of Smad ? (Fig. 1). These results suggest that Link-N exerts its growth factor-like effects via a BMP-signaling mechanism rather than TGF-β. Noggin is a known physiological negative modulator of BMP signaling and noggin levels are elevated in disease conditions. As we observed that Link-N signaling is similar to BMP, it is essential to assess if noggin can interfere with the function of Link-N. Dot-blot results showed that noggin does not directly bind with Link-N. Therefore, noggin inhibition of Link-N signaling is unlikely because of noggin binding with Link-N. This suggests that Link-N may have an added advantage as a therapeutic agent over BMPs. In addition, Link-N increased BMP 4 expression significantly in both AF and NP cells, with the increase in AF cells being significantly higher than that in NP cells. Specific binding (also internalization) of biotinylated Link-N was found both in AF and NP cells, as this binding was competitively displaced by nonbiotinylated Link-N. No binding was seen with scrambled biotinylated Link-N. Conclusion: Link-N represents a potential economic growth factor with beneficial effects on disc repair and the identification of the intracellular signaling pathways that it transduces is a step further toward clinical trials on NP repair in the degenerate human IVD. Disclosure of Interest None declared References Mwale F, Demers CN, Petit A, et al. A synthetic peptide of link protein stimulates the biosynthesis of collagens II, IX and proteoglycan by cells of the intervertebral disc. J Cell Biochem 2003;88(6):1202–1213 Gawri R, Antoniou J, Ouellet J, et al. Best paper NASS 2013: link-N can stimulate proteoglycan synthesis in the degenerated human intervertebral discs. Eur Cell Mater 2013;26:107-119, discussion 119 Mwale F, Masuda K, Pichika R, et al. The efficacy of Link N as a mediator of repair in a rabbit model of intervertebral disc degeneration. Arthritis Res Ther 2011;13(4):R120 Wang Z, Weitzmann MN, Sangadala S, Hutton WC, Yoon ST. Link protein N-terminal peptide binds to bone morphogenetic protein (BMP) type II receptor and drives matrix protein expression in rabbit intervertebral disc cells. J Biol Chem 2013;288(39):28243–28253